2007
DOI: 10.1097/rct.0b013e31803e8c67
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy Between the Dynamic Computed Tomography and T2* Magnetic Resonance Perfusion Imaging in Brain Tumors

Abstract: In this report, we separately performed dynamic computed tomographic perfusion and dynamic susceptibility contrast-T2 magnetic resonance perfusion imaging on 2 cases of brain tumors (one was a glioblastoma, and the other was a central neurocytoma). Between the 2 methods, we saw the discrepancy in values of cerebral blood volume and cerebral blood flow, differences in location of the maximal cerebral blood volume, and regions with abnormal increased cerebral blood flow besides the solid part of the tumors. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…There is surprisingly scant literature about perfusion MR imaging in patients with central neurocytoma. We found only two studies, both of which showed moderate elevation of rCBV (2–3) in intraventricular central neurocytomas . We did not find any study assessing the MR perfusion findings of extraventricular neurocytoma, though a recently published CT perfusion study reported low rCBV in a patient with extraventricular neurocytoma .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…There is surprisingly scant literature about perfusion MR imaging in patients with central neurocytoma. We found only two studies, both of which showed moderate elevation of rCBV (2–3) in intraventricular central neurocytomas . We did not find any study assessing the MR perfusion findings of extraventricular neurocytoma, though a recently published CT perfusion study reported low rCBV in a patient with extraventricular neurocytoma .…”
Section: Discussionmentioning
confidence: 66%
“…We found only two studies, both of which showed moderate elevation of rCBV (2-3) in intraventricular central neurocytomas. 12,13 We did not find any study assessing the MR perfusion findings of extraventricular neurocytoma, though a recently published CT perfusion study reported low rCBV in a patient with extraventricular neurocytoma. 14 We found the 1 p/19 q codeletion in both of our cases accompanied by a very high rCBV.…”
Section: Discussionmentioning
confidence: 90%